Peran Lembaga Kursus Pelatihan Primatari dalam Meningkatkan Eksistensi Tari Topeng Klana Gaya Slangit di Kabupaten Cirebon - Kressafanya Oktavianada; Restu Lanjari (Lembaga Pengembangan Kinerja Dosen, 2026)
The Slangit Style Klana Mask Dance in Cirebon Regency faces the threat of marginalization due to globalization and the lack of a successor generation. This study aims to analyze the role of the Primatari Training Course Institute (LKP) in maintaining and enhancing the existence of this traditional art. Using a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews with managers, trainers, and students, and documentation. The results of the study indicate that LKP Primatari has succeeded in maintaining sustainable dance through a beginner-friendly Slangit Style-based curriculum, ensuring the quality of the standard through the recruitment of internal trainers from senior alumni, and packaging routine training into periodic art performances in public spaces promoted through social media. A quarterly partnership relationship with the government and collaboration with the private sector also strengthen the appreciation of art spaces. Despite facing obstacles such as student saturation and still-organic innovation, this community-based management has proven effective in maintaining the existence of the dance. The implication is that an adaptive, non-formal training management model based on strategic partnerships can be an effective reference in preserving local cultural heritage in the modern era.